(untitled) (Research, Society and Development, 2020)
Due to the debate initiated in the 90s, regarding chemical waste in Brazilian Higher Education Institutions (HEI), it was possible to observe the abundance of problems related to this subject due to the lack of standardizing policies for the management of this waste in these institutions. It is known that the harmful practice of handling and improper disposal of these products can cause several difficulties in the environmental sphere and implies public health problems. As a result, this work aimed to study the chemical residues from the basic sector of the university city prof. José da Silveira Netto-UFPA. The research is a qualitative and quantitative study of an exploratory nature and was concluded after the execution of these five stages: characterization of the study area, waste inventory, application of questionnaires, field research and sampling of chemical residues. In the results it was possible to identify the sources of chemical waste in the Basic Sector of UFPA, in addition to diagnosing the amount that was 750 kg for expired packaging and 325 kg of contaminated bottles. In the qualitative analysis of management, the question of collection and treatment proved to be more worrying, as they are the main steps for environmentally appropriate management. Finally, recommendations were proposed to improve the management of chemical waste at the Institution, taking into account practices addressed by other HEIs that showed that it is feasible to carry out the management of chemical waste in an environmentally appropriate manner by proposing short, medium and long -term actions. long term.